Preclinical Dentistry Students' Knowledge And Attitude Towards Traumatic Dental Injuries (TDI) In Children At Syiah Kuala University - Vera Yulina; Ayudia Rifki; Maida Fitri (FKG Universitas Syiah Kuala, 2024)
Traumatic Dental Injuries (TDI) are medical emergencies that require immediate treatment. The accuracy of first aid during the golden time plays a role in the treatment outcome of TDI. This study aimed to investigate the knowledge and attitudes of Preclinical students regarding TDI in pediatric patients. This study administered an online questionnaire that had completed validity and reliability testing to all preclinical students (N=258). With a 95% confidence level (p0.05), a chi-square test was conducted on the data using SPSS software. First-year students had the lowest knowledge and attitudes toward TDI (68% and 54%, respectively). The degree of knowledge between preclinical students regarding the primary causes of TDI (61.1%), the need for immediate first aid in cases of avulsion (85.5%), an appropriate technique to hold avulsed teeth (91.5%), the selection of transport media (72.2%), storage medium (58.5%), and the urgency of receiving first aid for tooth fractures (60.3%) was significantly different. Regarding attitudes, there were significant differences in first aid actions, reimplantation, and attitudes toward selecting storage media, which were 60.7%, 62.8%, and 55.1%, respectively. The level of knowledge and attitudes of respondents towards TDI were low. Evaluation of learning methods, training implementation, and curriculum evaluation is needed.